NEW PROPOSAL ON THE PATHOGENESIS OF POSTERIOR REVERSIBLE ENCEPHALOPATHIC SYNDROME BASED ON DYSFUNCTIONAL PERICYTES - HUMBERTO FOYACA SIBAT, LOURDES DE FÁTIMA IBAÑEZ VALDÉS (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Introduction: The posterior region of the brain is primarily affected by the, a reversible white matter vasogenic oedema as the hallmark of this neurological condition named as PRES or reversible encephalopathy syndrome, which is a typical endothelial dysfunction, which modify the cerebral autoregulation, cause the before mentioned reversible subcortical vasogenic oedema, leading to headaches, confusion, seizures, and visual disturbances. Whether a drug can induce PRES The main goal of this review is to identify the novel diagnostic approaches and the most common drugs used. Methods: from January 01, 2006, to May 31, 2025, following the PRISMA guidelines we searched the medical literature. We checked some scientific databases like PubMed Central, Scopus and Embase looking for the titles: " posterior reversible encephalopathy syndrome " OR " pathogenesis of PRESS " OR " aetiology of PRES " OR " management of PRES", OR "The role of pericytes in PRES" Results: WE identified, 82 publications that were included in the final report. Notwithstanding, when we searched for PRES associated to Pcs dysfunction responding to drug therapy then no article was found. Conclusions: It is the first investigation done regarding to the role of PCs in the pathogenesis of PRES. We released some hypotheses related with the above issue.